Regional Innovation Sustainability Strategy through Integrated Innovation Governance: Case Study in Sukabumi City - Abdullah, Sait; Ahmad Mahalli , Raden; Nur Afandi, Muhamad (CV. Inara, 2024)
The sustainability of regional innovation is a problem in Sukabumi City, because the capacity and capability of human resources are still very limited and also the existing regional innovation system has not been integrated with each other. The purpose of this study is to identify the sustainability factors of regional innovation in Sukabumi City, analyze the sustainability process of regional innovation in Sukabum City. In this research on regional innovation sustainability strategies in Sukabumi City, researchers use exploration methods. Gulo (2010: 18), based on the results of the analysis, there are several factors that affect the sustainability of innovation in Sukabumi City, factors that support the sustainability of innovation in Sukabumi City, namely: resources, management systems, policies, leadership, and community participation. There is one important thing that becomes the findings of this research for the sustainability of innovation in Sukabumi City, namely Integrated Innovation Governance. Integrated Innovation Governance is an important part, because it involves easy public access to innovation. The recommendations of this study are the integration of innovation data into one innovation system (directory) through the expansion of data networks, the existence of documentation facilities and socialization of innovation results from innovation networks / stakeholders, the existence of easier facilities for the public to access innovation results, becoming an innovation information system to collect and store information on innovation results from all innovation networks, becoming a system for evaluation and selection of all innovations within the Sukabumi City Government.